2022
DOI: 10.3389/fendo.2022.942878
|View full text |Cite
|
Sign up to set email alerts
|

HemoglobinA1c Is a Risk Factor for Changes of Bone Mineral Density: A Mendelian Randomization Study

Abstract: BackgroundAs a valuable blood glucose measurement, HemoglobinA1c (HbA1c) is of great clinical value for diabetes. However, in previous observational studies, studies on its effect on bone mineral density (BMD) have different results. This study aimed to use Mendelian randomization (MR) to assess the effect of HbA1c on bone mineral density and fracture risk, and try to further explore whether this association was achieved through glycemic or non-glycemic factors.MethodsTake HbA1c measurement as exposure, and BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In a previous study, similar to diabetics, high prediabetics have lower trabecular bone score (TBS) than normoglycemic individuals [ 32 ]. And another study revealed the significant causal effect of HbA1c on BMD [ 33 ]. In insulin resistant states, insulin signaling leads to expansion of bone marrow adipose tissue and decreased trabecular BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, similar to diabetics, high prediabetics have lower trabecular bone score (TBS) than normoglycemic individuals [ 32 ]. And another study revealed the significant causal effect of HbA1c on BMD [ 33 ]. In insulin resistant states, insulin signaling leads to expansion of bone marrow adipose tissue and decreased trabecular BMD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between glycaemic control and bone fragility is controversial [ 23 , 24 , 25 ]. It is well known that some antidiabetic drugs affect bone metabolism, increasing fracture risk (sulfonylureas, thiazolidinediones and insulin treatment) [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the association between glycaemic control and bone fragility is controversial. Poor glycaemic control has been associated with lower bone mineralization in most studies [ 23 , 24 ], but not in others [ 25 ]. It is known that some antidiabetic drugs affect bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[38] In addition, Mendelian Randomization Pleiotropy Residual Sum and Outlier (MR-PRESSO) was performed to detect and correct for horizontal pleiotropy through removing outliers. [39] MR-PRESSO outlier test is based on the InSIDE assumption and requires that at least half of the IVs to be valid and has balanced pleiotropy. [40] Heterogeneity assessment of individual genetic variants was performed by Cochran Q statistic.…”
Section: Discussionmentioning
confidence: 99%